A Hierarchical Motion Planning for Mobile Manipulator. Issue 9 (16th July 2020) - Li, Qinghua; Mu, Yaqi; You, Yue; Zhang, Zhao; Feng, Chao
Abstract : This paper focuses on motion planning for mobile manipulators that can be used to plan both the base and the manipulator. An Optimized Hierarchical Mobile Manipulator Planner (OHMP) is proposed, which consists of two phases: two‐dimensional mobile base path planning and three‐dimensional manipulator trajectory planning. In the two‐dimensional mobile base path planning phase, a hybrid sampling strategy combining bridge test and uniform sampling is adopted to optimize Probabilistic Roadmap‐based basic planning and improve the efficiency of overall planning. In the three‐dimensional manipulator trajectory planning phase, if the current manipulator configuration is in a collision state, then a secure configuration is searched, and the trajectory between them is planned. Given start and goal configurations, the OHMP can efficiently produce a collision‐free path in complex environments. The estimates are backed up by the experiment result. It proves the validity and rationality of the planner, and it is effective for motion planning in complex static environments. © 2020 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.